Effects of volumetric efficiency on the performance and emissions characteristics of a dual fueled (gasoline and LPG) spark ignition engine - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
In this study, effects of variation in volumetric efficiency on the engine emissions characteristics with different LPG usage levels (25%, 50%, 75%, and 100%), on an engine operated with new generation closed loop, multi-point, and sequential gas injection system were investigated. For this purpose, experiments were carried out under constant engine speed (3800 rpm) and different load (5%, 30%, 60%, 90%) conditions. The variations in volumetric efficiency, air-fuel ratio, brake thermal efficiency, brake specific fuel consumption, brake specific energy consumption, and exhaust gasses were examined. The volumetric efficiency decreased considerably at the use of 25% LPG level. As for the 50%, 75% and 100% LPG usage, volumetric efficiency decreased in proportion to LPG usage level. Air-fuel ratio decreases with the increase in LPG usage level and the minimum air-fuel ratio value was obtained at 100% LPG usage. At the use of mixture containing 25% LPG, brake specific fuel and energy consumption decreased while the brake thermal efficiency was maintained. Positive results were obtained at all LPG usage levels in terms of exhaust emissions. Best results were achieved at using 100% LPG for exhaust emissions. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Volumetric efficiency; LPG; Gasoline; Dual fuel; Exhaust emissions; Engine performance; DIESEL-ENGINE; GAS; PARTICLE; VEHICLE